Insight of microRNA role in Colorectal Cancer - Kwan-Liang Lye; Loh Teng-Hern Tan; Hui-Min Yap (Progress in Microbes and Molecular Biology)
The colorectal cancer is among the most predominant cancer in the world including Malaysia. Numerous factors could contribute towards colorectal carcinogenesis and one of the factors is genetic predisposition. Mutations in the V-KiRas2 (Kras) oncogene have been implicated in 30-50% of the colorectal cancer patients and usually lead to poorer prognosis. The challenging ability for the early detection of colorectal cancer still poses an enormous challenge to oncologist as there are limited or no signs or symptoms in the early stage of colorectal cancer. Many studies were conducted hoping to further understand colorectal cancer for a better diagnosis and prognosis. As early detection of colorectal cancer frequently leads to good prognosis. The gold standard for prognosis depends on the stage of the tumor at the time of diagnosis. Lately a group of small, non-coding RNAs termed microRNAs (miRNAs) exhibited capable outcomes in cancer research. Numerous miRNAs were discovered to play a key role in regulatory mechanism in numerous cancers. Differential miRNAs expression among tumors and non-tumor controls are highly valuable in recognizing miRNAs that could have vital role in carcinogenesis. Recently some miRNAs were discovered to play a vital role in colorectal carcinogenesis. Thus, miRNAs have emerged as highly useful tool for scientists to comprehend carcinogenesis better. For example, miR-21 and miR-106a were highly expressed in colorectal cancer. While miRNAs including miR-17-92 cluster, miR-21, miR-34, miR-135 and miR-196a also exhibited high association with colorectal cancer. Therefore, this article aims to provide insight of miRNAs role in colorectal cancer for a better understanding of this disease.